Ответы и объяснения

2013-09-03T19:45:26+04:00
Выражение: (1+x)*(2+x)/x^2-x-2

Ответ: 2/x^2+3/x-1-x

Решаем по действиям:
1. (1+x)*(2+x)=2+3*x+x^2
  (1+x)*(2+x)=1*2+1*x+x*2+x*x
  1.1. x+x*2=3*x
  1.2. x*x=x^2
      x*x=x^(1+1)
    1.2.1. 1+1=2
          +1
           _1_
           2
2. (2+3*x+x^2)/x^2=2/x^2+3*x/x^2+x^2/x^2
3. x/x^2=x^(-1)
  x/x^2=x^(1-2)
  3.1. 1-2=-1
      -2
       _1_
      -1
4. x^(-1)=1/x
5. x^2/x^2=1
6. 1-2=-1
  -2
   _1_
  -1

Решаем по шагам:
1. (2+3*x+x^2)/x^2-x-2
  1.1. (1+x)*(2+x)=2+3*x+x^2
      (1+x)*(2+x)=1*2+1*x+x*2+x*x
    1.1.1. x+x*2=3*x
    1.1.2. x*x=x^2
          x*x=x^(1+1)
      1.1.2.1. 1+1=2
              +1
               _1_
               2
2. 2/x^2+3*x/x^2+x^2/x^2-x-2
  2.1. (2+3*x+x^2)/x^2=2/x^2+3*x/x^2+x^2/x^2
3. 2/x^2+3*x^(-1)+x^2/x^2-x-2
  3.1. x/x^2=x^(-1)
      x/x^2=x^(1-2)
    3.1.1. 1-2=-1
          -2
           _1_
          -1
4. 2/x^2+3/x+x^2/x^2-x-2
  4.1. x^(-1)=1/x
5. 2/x^2+3/x+1-x-2
  5.1. x^2/x^2=1
6. 2/x^2+3/x-1-x
  6.1. 1-2=-1
      -2
       _1_
      -1